CORPORATE INVESTMENT FINANCING AND FINANCIAL PERFORMANCE OF LISTED MANUFACTURING FIRMS IN NIGERIA (Journal of Global Accounting, 2025)
The study evaluated the effect of corporate investment financing on the financial performance of listed manufacturing firms in Nigeria. Specifically, the study determine the effect of equity financing, long term debt financing, short term debt financing and preferred stock financing on return on investment of manufacturing firms in Nigeria. Ex-post facto research design was used in the study. The purposive sampling was used to select a sample size of 29 firms over a thirteen year period that spanned from 2012 – 2024. Descriptive analysis was carried out together with correlational analysis, multicollinearity test, linearity test, autocorrelation test, cross-sectional dependence test, and heteroskedasticity test. The test of hypotheses was conducted using Panel Estimated Generalised Least Squares. The findings revealed that equity capital financing, long-term debt financing and short-term debt financing have a negative but significant effect on return on investment of manufacturing firms in Nigeria (β = -0.2611, p = 0.0000; β = -0.4857, p = 0.0000; and β = -0.2345, p = 0.0000), while preferred stock financing has a positive and significant effect on return on investment of manufacturing firms in Nigeria (β = 5.3326, p = 0.0213). In conclusion, when financing tools are structured with hybrid features that balance investor expectations with operational flexibility, firms may experience better financial outcomes. The study recommends that managers of listed manufacturing firms in Nigeria minimize reliance on equity financing unless absolutely necessary. They should consider other funding options to avoid dilution of ownership and reduce the negative impact on ROI.
Keywords: Corporate Investment Financing; Equity Financing; Financial Performance; Long Debt Financing; Preferred Stock; Short Debt Financing